Metacognition in ELT writing: Teacher’s facilitation and students’ strategies - Rimun, Jennifer Cristy; Yumarnamto, Mateus (Universitas Islam Negeri Banda Aceh, 2024)
Metacognition is central in understanding learning processes in the classroom, especially in the context of EFL writing. This study explores how an English teacher facilitated the mastery of metacognition strategies used by students in English writing classes, metacognitive strategies used by the students, and the impact of metacognitive strategies on students’ writing. The subjects were 17 eleventh grade students enrolled in the social program and their English teacher (one teacher) at a private school in Surabaya. The data were collected from students’ writing works, observation, and interviews. The data were coded and analyzed further by using thematic analysis. The findings reveal that the teacher played a role in fostering the mastery of metacognition skills in an English writing class by providing students with background knowledge, monitoring their progress, and encouraging an awareness of future tasks. With these types of facilitation, students could enhance their metacognitive strategies, such as using personal styles, planning, and self-evaluation. The findings show the importance of metacognition to promote students' awareness, self-regulation, and reflection. The findings imply that writing pedagogy should also involve in developing metacognition by means of effective teachers’ facilitation.